Educators' emotion regulation strategies and their physiological indicators of chronic stress over 1 year. (9th October 2017) - Katz, Deirdre A.; Harris, Alexis; Abenavoli, Rachel; Greenberg, Mark T.; Jennings, Patricia A.
Abstract: Studies show teaching is a highly stressful profession and that chronic work stress is associated with adverse health outcomes. This study analysed physiological markers of stress and self‐reported emotion regulation strategies in a group of middle school teachers over 1 year. Chronic physiological stress was assessed with diurnal cortisol measures at three time points over 1 year (fall, spring, fall). The aim of this longitudinal study was to investigate the changes in educators' physiological level of stress. Results indicate that compared to those in the fall, cortisol awakening responses were blunted in the spring. Further, this effect was ameliorated by the summer break. Additionally, self‐reported use of the emotion regulation strategy reappraisal buffered the observed blunting that occurred in the spring.